1985
DOI: 10.1159/000287868
|View full text |Cite
|
Sign up to set email alerts
|

Aggression in Depressives and Psoriatics

Abstract: The Questionnaire for Measuring Factors of Aggression (Fragebogen zur Erfassung von Aggressivitätsfaktoren, FAF) was completed by 113 depressive patients, 38 psoriatics, and 32 healthy controls. The controls had the lowest aggression scores, the neurotic depressives the highest. The monopolar endogenous depressives had extremely high scores for autoaggressions and extremely low ones for outward aggressions, whereas the psoriatics show a contrary tendency: extremely high scores for outward aggressions and very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
5

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 6 publications
4
17
0
5
Order By: Relevance
“…In relation to positive or negative emotions, our sample shows similar levels of negative affect but lower positive emotions than what has been reported in the general population [18], which could indicate that psoriasis patients suffer subclinical levels of psychopathology. This is in accordance with a classic study which found that psoriasis patients had intermediate levels of psychopathology when compared to depressed patients and healthy subjects [30]. The suggestion of intermediate levels of psychiatric diagnosis could partly explain why the psychological suffering of patients with psoriasis can go unnoticed to the healthcare professionals [8].…”
Section: Related Studiessupporting
confidence: 91%
“…In relation to positive or negative emotions, our sample shows similar levels of negative affect but lower positive emotions than what has been reported in the general population [18], which could indicate that psoriasis patients suffer subclinical levels of psychopathology. This is in accordance with a classic study which found that psoriasis patients had intermediate levels of psychopathology when compared to depressed patients and healthy subjects [30]. The suggestion of intermediate levels of psychiatric diagnosis could partly explain why the psychological suffering of patients with psoriasis can go unnoticed to the healthcare professionals [8].…”
Section: Related Studiessupporting
confidence: 91%
“…Regarding the dimension of general activity, female psoriasis patients showed higher scores than female atopic dermatitis patients. A previous report showed that psoriasis patients have high measures of outward aggression, which is compatible with our result . Bahmer et al .…”
Section: Discussionsupporting
confidence: 93%
“…A previous report revealed that Korean atopic dermatitis patients have a personality with distinct feelings of inferiority compatible with our study . In psoriasis, several studies showed no difference in personalities, while others showed a slightly distinctive temperament such as depression and nervousness …”
Section: Discussionsupporting
confidence: 91%
“…44 Psoriasis-related stress has been associated with greater psychiatric morbidity. 45 A wide range of psychologic characteristics have been reported in various crosssectional surveys, 14,35,[46][47][48] including high depression/anxiety scores, obsessionality, and difficulties with verbal expression of emotions, 40,49 especially anger, 40 social stigmatization, high stress levels, physical limitations, depression, employment problems, and other psychosocial comorbidities experienced by patients with psoriasis are not always proportional to, or predicted by, other measurements of disease severity, such as body surface area involvement or plaque severity. 50 Depression was highly associated with both illness-related stress and dissatisfaction with antipsoriatic treatment.…”
Section: Psychosocial and Emotional Stressmentioning
confidence: 99%